Local development scale. Case study north Valle del Cauca (Revista LIDER, 2020)
The study analyzes the local development in the northern area of the Cauca Valley, the challenges and opportunities for sustainable development. The study synthesizes approaches and conditions for development in the study area. The methodology consisted in the triangulation of information from secondary sources, semi-structured interviews and direct observation. The study concludes that the heterogeneity of municipalities and government policies that promote synergies in the direction of endogenous and inclusive development can reverse current conditions.